Showing where you're going. Instructing the accountable use of the indicator in live traffic. (9th January 2018) - Broth, Mathias; Cromdal, Jakob; Levin, Lena
Abstract : This article takes an interest in how students at a driving school are instructed how to make the car's behaviour intelligible ( accountable ) to other road users in traffic. Taking the indicator as an example, the analytic focus is on the ways in which the indicator's relevance is instructed and its timely activation practiced, and how activating the indicator is instructed as part of more encompassing turning procedures. The indicator is one of the central resources built into cars for displaying to others a driver's intention about where to go next. Although indicating does not, in itself, affect the movement of the car, activating the indicator is crucial for allowing others to anticipate a car's movement in space, and coordinate themselves with it. The analysis shows how instructors manage trainee drivers' instructed actions during driving by providing descriptions of what using the indicator accomplishes before a directive to turn (a), after a directive to turn (b), and as accounts for initiating correction of trainee driver car control activity (c).